Mental Illness at Work - Forms of Managerial Intervention (Global Journal of Medical Research, 2021)
Mental illness is still a gray area at most Austrian companies and remains associated with various stigmas, even though nearly one in every 10 days of sick leave is due to mental illness. This causes the phenomenon of presenteeism, and it also results in a considerable cost for the business and the economy as well as losses in productivity. Numbers of sick days taken due to mental illness are growing significantly, and this trend can only be counteracted with a corporate culture of openness, education, and destigmatization, and by taking the appropriate measures in all aspects of prevention. Both companies and politicians are therefore called upon to become proactive by creating the appropriate framework.
Keywords: mental illness; early intervention; presenteeism; awareness; destigmatization; workplace.